2008
DOI: 10.1186/1471-2229-8-126
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nitrogen and potassium nutrition on the growth of nonembryogenic and embryogenic tissue of sweet orange (Citrus sinensis (L.) Osbeck)

Abstract: Background: Mineral nutrients are one of the most basic components of plant tissue culture media. Nitrogen in the form of NH 4 + and NO 3 -is the dominant mineral nutrient in most plant tissue culture formulations, with effects dependent on both the proportion and the amount of NH 4 + and NO 3 -. The effects of nitrogen nutrition on the growth of nonembryogenic and embryogenic cell lines of sweet orange (C. sinensis (L.) Osbeck cv. 'Valencia'), tissues routinely used in citrus horticultural and plant improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Cell elongation was found to be associated with increased potassium [42]. Recently, Niedz and Evens [43] observed that K + nutrition is an important regulator for growth of embryogenic callus of sweet orange (Citrus sinesis (L.) Osbeck). In the present investigation, changes in the concentration of K in medium (potassium iodide form) led to a significant enhancement in the embryo yield and regeneration efficiency of P. ovata.…”
Section: Discussionmentioning
confidence: 98%
“…Cell elongation was found to be associated with increased potassium [42]. Recently, Niedz and Evens [43] observed that K + nutrition is an important regulator for growth of embryogenic callus of sweet orange (Citrus sinesis (L.) Osbeck). In the present investigation, changes in the concentration of K in medium (potassium iodide form) led to a significant enhancement in the embryo yield and regeneration efficiency of P. ovata.…”
Section: Discussionmentioning
confidence: 98%
“…R 2 , adjusted-R 2 (R adj 2 ), and predicted-R 2 (R pred 2 ), were estimated for each selected model (Myers and Montgomery 2002). Detailed descriptions of the statistical (Niedz and Evens 2008;. The software application Design-Expert® 7 (Stat-Ease, Inc, Minneapolis, MN) was used for experimental design construction, model evaluation, and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen form and concentration Historically, in cereal tissue culture, MS medium has been commonly used for plant regeneration and it contains a NH 4 + /K + ratio of 1. For this experiment, the two-component mixture of NH 4 + and K + and one quantitative factor NO 3 − amount were tested using a mixture amount design similar to Niedz and Evens (2008). Factor levels are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Transplanted T0 plantlets are grown to maturity, pollinated, and seed is harvested after approximately 3 to 4 mo problem of ion confounding between the effect of the Nsource, and the counter ion in that salt. Varying the ratio of NH 4 + /K + and the total nitrate concentration [NO 3 − ] in a twocomponent mixture, provided a direct estimation of mineral nutrient effects without the ion confounding of a salt-based approach (Niedz and Evens 2008). Potassium nutrition was also considered in this design.…”
Section: Introductionmentioning
confidence: 99%